Comparison Between Solvent Extraction Using Gas Chromatography Mass Spectrometry Triple Quadrupole (gcms-qqq) Of Cholesterol And Cholesterol Oxidation Derivatives - M.H.M. Yusop; Z. Norzaimah; Z.H. Shazamawati,; M.J. Thema Juhana; A. Siti Mashitoh; K.M.W. Syamsul; A.R. Alina (IDOSI Publications, 2024)
Middle-East Journal of Scientific Research 13 (Approaches of Halal and Thoyyib for Society, Wellness and Health): 43-48, 201